The border and associated problems - Fisk, E. K. (Ernest Kelvin); Australian National University. Research School of Pacific Studies (Canberra : Research School of Pacific Studies, Australian National University, 1974)
Three articles discussing the Papua-New Guinea Australia (Queensland) border dispute; E.K. Fisk and M. Tait - Rights, duties and policy in the Torres Strait; W.E. Holder - The Queensland border; the legal position; M.L. Treadgold - The economic significance of the disputed islands, each listed separately in the catalogue.
Processed.
Includes bibliographical references.
Keywords: Torres Strait Islands. Frontiers. Essays; Land rights - Claims, disputes, hearings; Law - Land - State and Territory - Queensland; Environment - Conservation - Law and legislation; Torres Strait Islands (Qld.) -- Boundaries; Papua New Guinea (PNG); Queensland (Qld); Torres Strait Islands (Qld TSI SC54, SC55-05)